"We Don't Got Time for Grumbling": Toward an Ethic of Radical Care in Urban School Leadership. (April 2021) - Rivera-McCutchen, Rosa L.
Purpose: This article presents a case study of a successful Black male public urban school principal, offering a counterstory to discourses of failure in urban schools. I build on scholars' work in critical caring, the Black principalship, and radical hope to call for an expansion of narrow frameworks of effective school leadership to include an ethic of radical care within urban school leadership.Method: This study represents a counterstory in the tradition of critical race theory, centering the voice and perspectives of a Black male urban school principal. Using ethnographic research methods, this case study was based on prolonged and embedded engagement in the field including observations, informal and formal interviews, and document review. Data were collected and analyzed over a 2-year period.Findings: Five components of effective school leadership emerged from analysis of the data that, taken together, can be described as a radical care framework. These components include the folowing: (a) adopting an antiracist, social just stance; (b) cultivating authentic relationships; (c) believing in students' and teachers' capacity for growth and excellence; (d) strategically navigating the sociopolitical and policy climate; and (e) embracing a spirit of radical hope.Conclusion: In addition to highlighting the power of counterstories in educational leadership research, this study reinforces the critical need for leadership preparation that is grounded in antiracism and social justice, and comprises all aspects of an ethic of radical care. Furthermore, the study points to the need for targeted recruitment of Black and Latinx school leaders, particularly in urban contexts.